Juridical Review of the Legal Imposition of the Defendant in the Sued Divorce Case as the Implementation of Just PERMA No. 3 of 2017 - Trubus Wahyudi; Masrur Ridwan (Journal of Advanced Multidisciplinary Research, 2020)
The law enforcement paradigm regarding the legal imposition of the Defendant in the case of sued divorce lawsuit as the implementation of Perma No. 3 of 2017, the factor of law protection and justice for women and children's rights due to the divorce of their parents in the Religious Court is essential as the upholding of the rule of law and justice. Judges in adjudicating women's cases against the law must adhere to the following principles: respect for human dignity, non-discrimination, gender equality, equality before the law, justice, benefit and legal certainty. The process of adjudicating a divorce case, even if the initiative of the case is from the woman, her rights must be protected by the former wife, as well as the rights of her child. Normatively, the legal arrangements for the divorce case are Article 73 to Article 83 of Law Number 7 of 1989 Jonto Article 114 to Article 156 Compilation of Islamic Law, and as the initiator of the filing of the divorce case is the wife as the plaintiff. This study uses a sample of several decision objects in certain Religious Courts in the jurisdiction of the High Court of Religion, Central Java, through a series of research methods with a sociological juridical approach or social legal research, and data collection techniques through interviews and literature study. The implementation of Perma No. 3 of 2017 regarding the legal imposition of the Defendant in the case of sued divorce lawsuit in the Religious Court can be formulated in the form of a dictum of the Judge's decision "Condemnatur" as a court product that contains the rights of the former wife as the Plaintiff, as well as the rights of child support, fees sustainability of education and health that is just.